The Implementation of Digital Image Steganography in Identifying the Originality of Digital Certificates Using the Least Significant Bit (LSB) Method - Kurniawan R, Rakhmat; Sriani; Ibsan, Muhammad Hanafi (Bahasa Indonesia, 2023)
Technological developments mean that data and information are presented in digital form, such as the use of digital certificates. Digital certificates are widely used by agencies that hold online seminars or training, so seminar participants will be given digital certificates. The large number of uses of digital certificates can influence the misuse of these certificates by counterfeiting digital certificates, so it is necessary to secure digital certificate data using steganography. Steganography is not only used to hide information, but also to protect copyright and the authenticity of an image. The hidden secret data is in the form of images, audio, text or video. The image steganography process is carried out using the Least Significant Bit (LSB) method. LSB works by replacing the original image bits with information bits that will be hidden. LSB is a method that can be applied in cases of identifying the authenticity of digital certificates because the image of a digital certificate that has undergone steganography does not change much of the original image and cannot even be distinguished by the naked eye. However, LSB cannot be used on jpg format data, this is because LSB is unable to extract messages that have been inserted into digital certificate images in jpg format.